Injuries during a World Judo Championship: differences between sex, weight category and competition phase - Miarka, B.; Dal Bello, F.; Brito, C. J.; Tabben, M.; Oguma, A.; Amtmann, J.; Gomes Moreira, D.; Pocecco, E.; Boscolo del Vecchio, F.; Chamari, K. (International Journal of Performance Analysis in Sport, 2018)
This study analyses the injury incidence and related factors during the World Judo Championship of 2013. For this purpose, 673 athletes (258 females and 415 males) of all weight categories have been evaluated concerning factors related to occurred injuries (severity, body area, situation, type and mechanism) in an epidemiological observational study. Concussions were identified and analysed separately for injury risk and incidence rate per 1000 A-E (athlete-exposures). ANOVA, Tukey, Chi-squared and a Logistic Regression Analysis were performed, p = .05. The overall incidence rate was of 47.2 injuries. The incidence rate separated by sex was 38.0 and 52.9 for males and females, respectively. There was a higher prevalence of soft-tissue injuries (58.8%) characterised as stress injuries (36.8%) and miscellaneous traumas (42.6%), mostly occurring during being thrown (29.4%) and gripping fight (32.4%). Concerning the phases of the competition, there was a higher prevalence of injuries in the Eliminatory (54.4%) followed by the Final (20.6%). Male athletes had a prevalence of injury mechanism "contact with mat", while an increase in the weight division was negatively associated with the incidence of miscellaneous traumas, musculoskeletal injuries and neck chokes. These risks in competitions could be minimised with prevention systems.